ANALISIS PERILAKU PERUSAHAAN DALAM PASAR OLIGOPOLI DI INDUSTRI OTOMOTIF - Hikmah Al Mustofiyah; Yulisa Tri Hapsari; Naerul Edwin Kiky Aprianto (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the structure and behavior of companies in the oligopoly market in the automotive industry. In the context of the automotive industry, the oligopoly market is characterized by a small number of companies that have a large share such as Toyota, Honda, Daihatsu etc. The oligopoly market is so competitive that technology and other facilities are considered to be very influential in introducing the company's products. The type of research used in this article is descriptive qualitative research. Data collection is carried out through a combination of various techniques, with inductive data analysis. The results of the analysis show that the interdependence between companies creates price stability, but also hinders healthy competition. In addition, the high barriers to entry for newcomers also reinforce the dominance of large companies in the market.